The Influence of Head of Village Leadership and Tax Administration Sanctions on Public Awareness in Efforts to Pay Land and Building Tax in Sayurmatinggi Village, Batangonang Sub-District, Padanglawas Urata District - Harahap, Nurasiyah; Rambe, Saima (Pengurus Pusat Perkumpulan Ilmuwan Administrasi Negara Indonesia (PIANI), 2024)
Abstract This research aims to analyze the influence of the Village Head's leadership and tax administration sanctions on public awareness in paying Land and Building Tax (PBB). Data was collected through a questionnaire distributed to 22 taxpayer respondents. The results of the analysis show that the validity test results for each questionnaire item are valid with a calculated r value greater than r table, and the reliability test shows that the Cronbach's Alpha value is above 0.60, which means it is reliable. Classic assumption tests include normality, multicollinearity and autocorrelation tests, where the data is normally distributed and there is no multicollinearity (VIF < 10). The results of the T test show that the leadership of the Village Head (XI) has a significant effect on public awareness (Y) with a t-value of 6.405 < 0.05, and tax administration sanctions (X2) also have a significant effect with a t-count of 3.583 < 0.05. The leadership of the village head (XI) has a significant effect on paying land and building taxes (Z) with a t-count of 4.508 < 0.05 and administrative sanctions for taxes (X2) also have a significant effect with a t-count of 6.548 < 0.05. The F test shows the simultaneous influence of the two independent variables on public awareness, with an F count of 29.486 and a significance of 0.001. The coefficient of determination (R²) of 0.831 indicates that 83.1% of the variation in community awareness can be explained by the leadership of the village head and tax administration sanctions. Keywords: Village Head Leadership, Tax Administration Sanctions, Community Awareness, Land and Building Tax (PBB).